2013
DOI: 10.1186/1755-8794-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Genomic pathway analysis reveals that EZH2 and HDAC4 represent mutually exclusive epigenetic pathways across human cancers

Abstract: BackgroundAlterations in epigenetic marks, including methylation or acetylation, are common in human cancers. For many epigenetic pathways, however, direct measures of activity are unknown, making their role in various cancers difficult to assess. Gene expression signatures facilitate the examination of patterns of epigenetic pathway activation across and within human cancer types allowing better understanding of the relationships between these pathways.MethodsWe used Bayesian regression to generate gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…It has been reported that microenvironmental changes play a role in regulating cell behavior, which eventually causes epigenetic disorders in cancer cells (34,35). Additionally, we found that both protein and mRNA of p21 are suppressed when epithelial ovarian cancer cells are seeded on fibrillar collagen.…”
Section: Discussionsupporting
confidence: 49%
“…It has been reported that microenvironmental changes play a role in regulating cell behavior, which eventually causes epigenetic disorders in cancer cells (34,35). Additionally, we found that both protein and mRNA of p21 are suppressed when epithelial ovarian cancer cells are seeded on fibrillar collagen.…”
Section: Discussionsupporting
confidence: 49%
“…Activity of HDAC is generally linked to transcriptional repression . The misbalance in HDAC activity is associated with cancer and several disorders including fibrosis, with aberrations in inflammatory and chemokine‐related genes . Specifically, HDAC4 has been related to fibrogenesis in vivo and, as we mentioned before, in PBC patients with low expression of PHB1.…”
Section: Discussionmentioning
confidence: 72%
“…We observed that HDAC4 expression was strongest for the cytoplasmic area and intensity in uveal melanoma. HDAC4 is often upregulated in malignancies with excess inflammation and chemokine signalling [30], consistent with an inflammatory phenotype known to enhance the progression of uveal melanoma [31]. In some immune cells, controlled nuclear export of HDAC4 plays an important role in cytokine production [28].…”
Section: Discussionmentioning
confidence: 99%